2020
DOI: 10.1074/jbc.ra120.015325
|View full text |Cite
|
Sign up to set email alerts
|

Exosite binding drives substrate affinity for the activation of coagulation factor X by the intrinsic Xase complex

Abstract: Factor X activation by the intrinsic Xase complex, composed of factor IXa bound to factor VIIIa on membranes, is essential for the amplified blood coagulation response. The biological significance of this step is evident from bleeding arising from deficiencies in factors VIIIa or IXa in hemophila. Here, we assess the mechanism(s) that enforce the distinctive specificity of intrinsic Xase for its biological substrate. Active site function of IXa was assessed with a tripeptidyl substrate (PF-3688). The reversibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
(60 reference statements)
0
11
0
Order By: Relevance
“…In our studies, we used the inhibitor EGRck to assess the effect of active site occupation in FIXa. Binding of the natural substrate FX, however, is more complex and probably also involves exosites distant from the active site 46 . Therefore, substrate‐driven changes in FIXa may be more extensive than we observed in active‐site inhibited FIXa.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In our studies, we used the inhibitor EGRck to assess the effect of active site occupation in FIXa. Binding of the natural substrate FX, however, is more complex and probably also involves exosites distant from the active site 46 . Therefore, substrate‐driven changes in FIXa may be more extensive than we observed in active‐site inhibited FIXa.…”
Section: Discussionmentioning
confidence: 63%
“…Binding of the natural substrate FX, however, is more complex and probably also involves exosites distant from the active site. 46 Therefore, substrate-driven changes in FIXa may be more extensive than we observed in active-site inhibited FIXa. Further studies could dissect substrate-and cofactor-driven changes in more detail.…”
Section: Discussionmentioning
confidence: 65%
“…The intrinsic tenase activation of FX is driven by exosite binding [7], and as previous studies have suggested that the FX‐AP contributes to activator specificity and prevents the promiscuous activation of FX [8,11,19], the FX‐AP may be an important exosite. This was demonstrated in a competitive inhibition study, where a chimeric FX construct containing human FX and the AP of venom‐derived Pseudonaja textilis was a significantly weaker competitor of the intrinsic tenase‐mediated activation of human FX, compared with a nonactivable FX construct containing a Gln substitution of the Arg residue at the P1 site [12].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the contribution of interdomain interactions to protease conformational changes upon activation remain incompletely described. Second, while incorporation of EGR‐ck recapitulates a portion of the substrate interaction with the active site, FX activation by the intrinsic tenase complex involves exosite‐mediated substrate recognition, which likely induces additional conformational changes that contribute to activation of FIXa catalysis 17 . Finally, limitations in the sensitivity of the HDX‐MS approach exist due to back‐titration of deuterium during peptide processing.…”
Section: Figurementioning
confidence: 99%
“…Reduced deuterium uptake was noted for three α-helixes located in the basic exosite II of FIXa (Figure 1 changes that contribute to activation of FIXa catalysis. 17 Finally, limitations in the sensitivity of the HDX-MS approach exist due to backtitration of deuterium during peptide processing.…”
mentioning
confidence: 99%